Pengaruh Perbedaan Periode Aerasi Karbondioksida terhadap Laju Pertumbuhan dan Kadar Total Lipid pada Kultur Nannochloropsis oculata - Norbawa, Puji; Yudiati, Ervia; Widianingsih, Widianingsih (977-2407769)
N. oculata is commonly used as a natural food in larviculture. Due to the fact on its highly lipid content, N. oculata is recently becoming one of a good candidate for a source of alternative energy. Microalgae utilizes CO2 during photosynthesis. This fact will lead and used this microalgaeas a carbondioxide degradator. Providing of carbon dioxide aeration is expected to increase the rate of growth of N. oculata as well as total lipid production.This research aimed to determine the effect of different periods on carbondioxide aerationon the growth rate and total lipid production in N. oculata culture.The results showed that different time on carbondioxide aeration was significantly different (P < 0.05) on the average growth rate as well as total lipid production. Carbondioxide aeration treatment for 3 minutes have the highest average growth rate which is0,574 doubling/ day. While the average growth rate at treatment aeration for 4 minutes almost equal to the control i.e. 0,484 doubling/ day and 0,462 doubling/ day. The highest percentage of total lipid production has reached in 4 minutes carbondioxide aeration treatment (80.58%-dw). Furthermore, the lipid production on 1 minute, 2 minutes aeration time and control were 65.98%-dw, 65.77%-dw and 64.98%-dw, respectively. The treatment with carbondioxide aeration for 3 min was the lowest (39.72%-dw). Based on these results it can be concluded that carbondioxide aeration for 3 minutes increased the growth rate of N. oculata. However, the incrementon growth ratewere not accompanied withthe incrementon total lipid production.